Relative Motion between St. Croix and the Puerto Rico-Northern Virgin Islands Block Derived from Continuous GPS Observations (1995–2014) - Hanlin Liu; Guoquan Wang (International Journal of Geophysics)
St. Croix is located inside the sweep of the Lesser Antilles arc and near the southeastern edge of the Greater Antillean ridge. It is separated from the Puerto Rico and the Northern Virgin Islands (PRNVI) block by the Virgin Islands basin. Recent seismic activities demonstrate that the Virgin Islands basin is tectonically active. A better understanding of fault activities in the basin would improve seismic hazard assessment in this region. This study illustrates out a detailed way of deriving relative motion between St. Croix and the PRNVI block using current GPS geodesy infrastructure in the PRVI region. The local geodesy infrastructure includes over 20 continuous GPS stations and a Stable PRNVI Reference Frame (SPRNVIRF). Twenty-year continuous GPS observations (1995–2014) on St. Croix indicate that the island is presently moving away from the PRNVI block toward the southeast (S55°E) at a steady rate of 1.7 mm/year. The velocity vector can be decomposed into two 1.2 mm/year components along the long-axis and short-axis directions of the rhomboidal Virgin Islands basin. Quantitative results indicate that the Virgin Islands basin presently experiences left-lateral motion in a nearly east-west direction and extension in a nearly north-south direction.